Studi Kasus: Identifikasi Kasus Penyakit pada Ayam Broiler di Pasar Naikoten, Kota Kupang - Ola, Elisa Albertine Rahmita Deran; Gelolodo, Maria Aega (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Diverse diseases can impede the development of the poultry industry; therefore, it is essential to identify and analyze the causes of these diseases through thorough examinations. Laboratory examinations of parasites, viruses, and bacteria are essential for the diagnosis of diseases in poultry. This procedure allows an improved diagnosis, enabling appropriate treatment administration and the design of preventative strategies to mitigate disease transmission risk. A white broiler chicken with a body condition score of 3/5 that was purchased at Pasar Naikoten in Kota Kupang is the case animal. The chicken has exhibited illness for five days, presenting symptoms including footpad wounds and swelling, lethargy, reduced appetite, weight loss, dull plumage, limping, and occasional neck deformity. A series of virology and bacteriology laboratory tests confirmed a positive diagnosis of Bumblefoot caused by Staphylococcus aureus infection, with a differential diagnosis of Newcastle disease based on clinical symptoms. Therapy was not conducted as the case chicken had already been sold by the trader; therefore, only educational efforts for sellers concerning the risk factors for disease occurrence were implemented.